2019
DOI: 10.1136/bmjopen-2018-028497
|View full text |Cite
|
Sign up to set email alerts
|

Statistical projection methods for lung cancer incidence and mortality: a systematic review

Abstract: ObjectivesTo identify and summarise all studies using statistical methods to project lung cancer incidence or mortality rates more than 5 years into the future.Study typeSystematic review.MethodsWe performed a systematic literature search in multiple electronic databases to identify studies published from 1 January 1988 to 14 August 2018, which used statistical methods to project lung cancer incidence and/or mortality rates. Reference lists of relevant articles were checked for additional potentially relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 119 publications
0
28
0
Order By: Relevance
“…Selecting an appropriate projection method mainly relies on data availability and the purpose of the forecasts. These methods range from the present state method assuming the current rate remains unchanged into the future to more complex statistical models of historical trends, including APC and generalized linear mixed model (GLMM) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selecting an appropriate projection method mainly relies on data availability and the purpose of the forecasts. These methods range from the present state method assuming the current rate remains unchanged into the future to more complex statistical models of historical trends, including APC and generalized linear mixed model (GLMM) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The APC model is the most commonly used projection method for lung cancer incidence and remains appropriate for long-term projections [ 28 ]. Period effects can represent screening, diagnostic, and treatment factors that led to lung cancer incidence variation across all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review identified 101 studies published between 1st January 1988 and 14th August 2018 that used statistical methods to project lung cancer incidence or mortality rates (Yu et al, 2019). The aims of this study were to compare previously published lung cancer incidence and/or mortality rate projections to observed data that became available since their publication, and to provide insights into key factors that should be considered when selecting methods for projecting lung cancer rates.…”
Section: How Well Have Projected Lung Cancer Rates Predicted the Actumentioning
confidence: 99%
“…The literature search (Online resource 1) and review protocol for potentially relevant studies are described in detail in our previously published systematic review (Yu et al, 2019), and the full inclusion and exclusion criteria are summarised in Online resource 2. The results of the literature search and the process for selecting studies are described in Online resource 3.…”
Section: Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation